2009
DOI: 10.1523/jneurosci.0822-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Regulates Oligodendrocyte Development

Abstract: In the postnatal brain, oligodendrocyte progenitor cells (OPCs) arise from the subventricular zone (SVZ) and migrate into the developing white matter, where they differentiate into oligodendrocytes and myelinate axons. The mechanisms regulating OPC migration and differentiation are not fully defined. The present study demonstrates that endothelin-1 (ET-1) is an astrocyte-derived signal that regulates OPC migration and differentiation. OPCs in vivo and in culture express functional ET A and ET B receptors, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 100 publications
6
77
3
Order By: Relevance
“…The results showed that the numbers of Olig2/BrdUdouble-positive cells are unchanged in the SVZ but are reduced in the Fim and CC in the N-Arf6-CKO mice. These results led to the conclusion that neuronal Arf6 plays an important role in OPC migration from the SVZ to the Fim and CC but not in NSC proliferation/differentiation, consistent with reports that OPCs differentiated from NSCs in the SVZ migrate to target areas in the postnatal brain [19][20][21][22][23] . However, it is still possible that proliferative NSCs in brain regions other than the SVZ differentiate into OPCs that migrate to the Fim and CC.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that the numbers of Olig2/BrdUdouble-positive cells are unchanged in the SVZ but are reduced in the Fim and CC in the N-Arf6-CKO mice. These results led to the conclusion that neuronal Arf6 plays an important role in OPC migration from the SVZ to the Fim and CC but not in NSC proliferation/differentiation, consistent with reports that OPCs differentiated from NSCs in the SVZ migrate to target areas in the postnatal brain [19][20][21][22][23] . However, it is still possible that proliferative NSCs in brain regions other than the SVZ differentiate into OPCs that migrate to the Fim and CC.…”
Section: Discussionsupporting
confidence: 90%
“…There are an increasing number of pathways and mechanisms being identified that could potentially play similar roles [85][86][87][88]. As previously indicated, such research could impact not only MS, but other myelin disorders, such as periventricular leukomalacia (PVL), in which a critical window for repair is inadequately addressed by current therapies.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Focal injection of ET-1 using the approach described here has been reported but endothelin-1 was shown to have direct paracrine effects on oligodendrocyte differentiation and maturation 10,18 confounding the study of post-stroke white matter biology. In contrast, the L-Nio approach targets endothelial cells alone while producing an identical lesion and eliminates any confounding paracrine effects on the cells involved in injury response.…”
Section: Discussionmentioning
confidence: 96%
“…The major advantages of this model are the use of a chemical endothelial nitric oxide synthase (eNOS) inhibitor N(5)-(1)-iminoethyl-L-ornithine HCl (L-Nio) 9 with no known paracrine effects on cellular elements of white matter which had been a complication of models using endothelin-1 10 . In addition, the stereotactic targeting of white matter in the mouse allows the use of any variety of transgenic or knockout strains, greatly expanding the available tools to determine the effect of stroke on brain white matter.…”
Section: Introductionmentioning
confidence: 99%